Assistance with Financial Aspects and Marketing Strategy at DINDA BUMDes in Sumenep Regency - Aprilya Dwi Yandari; Kurniawan Novianto; Isnani Yuli Andini; Endang Widyastuti; Laurentia Maria Husada (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of holding this activity is to provide good and correct direction in terms of financial administration, good marketing, and analyze the potential that exists in the local area so that it becomes additional income for BUMDesa DINDA. The method used is the initial stage of conducting a location survey, then the team conducts pre-research to resolve problems and potential that exists in the object, the third stage provides assistance, training, or outreach regarding existing problems, and the team stage evaluates the results of activities such as bookkeeping reports good and right finance, good form of promotion, concept of evaluating prospects of potential activity with location. This was carried out for almost two months, so that the results of the dedication really helped the local BUMDesa management and were able to implement it properly and correctly according to existing standards or rules